2020
DOI: 10.21037/tau-20-1154
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for predicting prostate cancer in men with prostate-specific antigen grey zone based on retrospective analysis of clinical and multi-parameter magnetic resonance imaging/transrectal ultrasound fusion-derived data

Abstract: Background: Urologists face a dilemma when deciding whether prostate biopsy is required for patients with prostate-specific antigen (PSA) levels in the grey zone (4 to 10 ng/mL). Methods:We retrospectively analyzed data from consecutive patients with PSA levels in grey zone, who underwent targeted multiparametric magnetic resonance imaging (MP-MRI)/transrectal ultrasound (TRUS) fusion biopsy with elastography between November 2017 and December 2019 in our hospital. The patientse data including age, PSA, fPSA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Earlier research found that when PSA was in the diagnostic gray zone, PI-RADS had a better predictive ability than %fPSA and PSAD to avoid unnecessary prostate biopsies in patients, and PI-RADS score was complementary to PSAD and%fPSA. 30 , 35 , 36 Xu et al . 30 discovered that PI-RADS score of 4 was the best threshold for predicting csPCa, with a relatively low NPV of 0.716.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research found that when PSA was in the diagnostic gray zone, PI-RADS had a better predictive ability than %fPSA and PSAD to avoid unnecessary prostate biopsies in patients, and PI-RADS score was complementary to PSAD and%fPSA. 30 , 35 , 36 Xu et al . 30 discovered that PI-RADS score of 4 was the best threshold for predicting csPCa, with a relatively low NPV of 0.716.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, especially for nations with lower prostate cancer incidence rates, the prostate volume should be considered when counseling patients regarding their prostate cancer risks. 27 Our results highlight the significance of prebiopsy MRI, indicating that PI-RAD scores help decide on biopsy and prognosis of prostate cancer.…”
Section: Nomograms Have Been Developed and Validated In Previousmentioning
confidence: 58%
“…Based on 345 cases of grey zone, Fang et al 26 established a score for prostate volume, age, MRI, and DRE that had good prediction accuracy for high‐grade prostate cancer. Higher PI‐RAD scores occupied the second rank after lower free PSA/total prostate‐specific antigen (tPSA) ratio, and prostate volume in the nomogram forecasting the possibility of prostate cancer, in the study conducted by Ding et al 27 …”
Section: Discussionmentioning
confidence: 99%
“…Comparing with the traditional strain elasticity, EQS has higher accuracy and better repeatability. Our previous research showed that the EQS could improve the accuracy of diagnosing, grading PCa (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%